BAM FORM 6 – MATRICES

Share this post on:

 is an arrangement of number in rows and columns. Its usually denoted using capital letters
E.g A = edu.uptymez.com          B = edu.uptymez.com         C =edu.uptymez.com

Order: A matrix is said to be of order m x n if it has m rows and n columns.

E.g. Order of A is 2 x 2

       Order of B is 3 x 3

       Order of C is 2 x 3

Types

      Rows matrix is a matrix with only one row.

e.g. D = (2 1 6)

      Column matrix is a matrix with only one column.

E.g.   Д = edu.uptymez.com

      Square matrix  is a matrix with equal number of rows and column

E.g.  A = edu.uptymez.com                B = edu.uptymez.com

      Identity matrix (T) is a square matrix with all elements in the  leading diagonal equals to 1 and the rest are 0.

E.g. I = edu.uptymez.com 

                   I = edu.uptymez.com

Property

AI = A

Null (zero) matrix (Z) is a matrix with all elements equation to 0 e.g.  Zedu.uptymez.com

            Properties

            1) A + Z = A

            2) AZ = Z

            Operations

i) Addition/ subtraction

   This is only possible if the matrices have the same order

E.g.    A = edu.uptymez.com        B = edu.uptymez.com
edu.uptymez.com

ii) Scalar multiplication

            Given a scalar multiplication then

            A = t edu.uptymez.com

            =   edu.uptymez.com

E.g.: Evaluate tP – sQ

Given t = 3 s = ½, P = edu.uptymez.com

                               Q = edu.uptymez.com

Solution

            tP – SQ
edu.uptymez.com


edu.uptymez.com

   iii) Product
   AB is only possible if the order of A is m x n and that of B is n x p and  the resulting matrix will be of the order m x p.

e.g.      i) edu.uptymez.comedu.uptymez.com

            2 x 2        2 x 1

            edu.uptymez.com

            ii) edu.uptymez.comedu.uptymez.com

                        edu.uptymez.com

E.g.      edu.uptymez.comedu.uptymez.com

                3 x 3         3 x 1

=   edu.uptymez.com

edu.uptymez.com  = edu.uptymez.com

                iv) edu.uptymez.com    edu.uptymez.com

                           3 x 3                        3 x 3

    edu.uptymez.com


E.g.   edu.uptymez.com edu.uptymez.com

    3 x 3                3 x 3

edu.uptymez.com                       

=edu.uptymez.com

Determinant of a 2 x 2 matrices

   Given A =edu.uptymez.com

Determinant of A = edu.uptymez.com

                          = edu.uptymez.com


= ad – cb

If the determinant A = 0 then A is singular matrix

            E.g. which of the following is singular or non singular matrix

A = edu.uptymez.com

edu.uptymez.com


8 – 9 = -1     Non – singular matrix

    B = edu.uptymez.com

  edu.uptymez.com = 1(6) – 2(3)

        = 6 – 6

        = 0       Singular matrix

C = edu.uptymez.com

edu.uptymez.com

   = 8   Non – singular matrix

Inverse of a 2 x 2 matrix

            Given A = edu.uptymez.com

The inverse of A = A-1
edu.uptymez.com

        E.g.      A = edu.uptymez.com
edu.uptymez.com
edu.uptymez.com = 2 (4) – 3(3) = -1

        edu.uptymez.com
edu.uptymez.com

           A-1 =edu.uptymez.com


A-1 =edu.uptymez.com

Solving system of simultaneous equations in 2 unknowns

Given the following equations
edu.uptymez.com

In a matrix form

            edu.uptymez.com edu.uptymez.com = edu.uptymez.com

Determinant method

1.  (Cramer’s rule)

            Solving for x

             edu.uptymez.com    where

           edu.uptymez.comand edu.uptymez.com
Solving for y
edu.uptymez.comwhere
edu.uptymez.comand edu.uptymez.com

            E.g. solving the following using Cramer’s rule

                        x + y = 3

                        x – y = 1

edu.uptymez.com edu.uptymez.com   =  edu.uptymez.com

A= edu.uptymez.com    Δ  = 
edu.uptymez.com = 1 (-1) – (1)= -2

             edu.uptymez.com    where edu.uptymez.com

                   edu.uptymez.com

            edu.uptymez.com
Δ  = 
edu.uptymez.com = 1 (-1) – (1)= -2

             edu.uptymez.com
edu.uptymez.com
edu.uptymez.com = edu.uptymez.com

2.   Inverse method

            edu.uptymez.com edu.uptymez.com = edu.uptymez.com

            edu.uptymez.com = A-1  edu.uptymez.com

edu.uptymez.com

          edu.uptymez.com
E.g.  x + y = 3

                    x – y = 1

            edu.uptymez.com   edu.uptymez.com = edu.uptymez.com

            A = edu.uptymez.com edu.uptymez.com = -1(1) – 1 (1) = -2

edu.uptymez.com

edu.uptymez.com

A-1 = edu.uptymez.com

                  A-1 = edu.uptymez.com

                edu.uptymez.com  =  edu.uptymez.com    edu.uptymez.com

                     = edu.uptymez.com

                        = edu.uptymez.com

                        = edu.uptymez.com

                        = edu.uptymez.com

                        edu.uptymez.com = edu.uptymez.com

Determinant of a 3 x 3 matrix

Given A = edu.uptymez.com


edu.uptymez.com

            = a edu.uptymez.com – b edu.uptymez.com + c edu.uptymez.com

            edu.uptymez.com = a (ek – fh) – b (dk – fg) + c (dh – eg)

E.g  Find edu.uptymez.comgiven B = edu.uptymez.com

edu.uptymez.com

                   = 3 edu.uptymez.com  – (-1) edu.uptymez.com + 2 edu.uptymez.com

                   = 3 (3 + 8) + 1(0 – 20) + 2 (0 – 5)

                  = 33 – 20 – 10

                  = 3                                                                                                     

                  edu.uptymez.com = 3

Transpose
                    edu.uptymez.com

                  edu.uptymez.com

E.g,    B = edu.uptymez.com

                        BTedu.uptymez.com


Co factors

                        A =edu.uptymez.com

 A co factor of an element in a 3 x 3 matrix is given by determine determinant of a 2 x 2 matrix which is formed by removing elements in the same row and column with given element and multiply by 1 or -1 according to the following procedure.

            Produce  edu.uptymez.com

            E.g. C = edu.uptymez.com
   edu.uptymez.com

                        = (3 + 8) = 11

          Cof  0         -1 edu.uptymez.com

                           = -1 (-3 + 4) = -1

edu.uptymez.com

                         = + (-4 – 2) = -6

            Cof (-1)      -1edu.uptymez.com

                           = -1 (0 – 20) = 20

               Cof 1  + 1 edu.uptymez.com

                        = 1 (9 – 10) = -1

            C0f -2

                        -1 edu.uptymez.com

                        = -1 (12 – 0) = -12

            Cof 2

                        1 edu.uptymez.com

                        = 1 (0 – 5) = -5

            Cof 4

                        -1 edu.uptymez.com

                        = -1 (-6 + 5) = 1

            Cof 3

                        1 edu.uptymez.com

                        = 1 (3 + 0) = 3

Matrix of Cofactors
 
  A = edu.uptymez.com

edu.uptymez.com


        Adjoin of A = adj,    AT = the transpose of matrix of Cofactors
edu.uptymez.com
Inverse of A

        edu.uptymez.com

Summary

   Procedure for finding inverse of a 3 x 3 matrices

    i) Find the determinant

   ii) Find the cofactors

   iii) Form the matrix of cofactors

   iv) Form the adjoint

    v) Find the value

Solving simultaneous equation in 3 unknown

1. Determinant method (Cramer’s rule)

            Given that       a1x + by + c1z = p

                                    a2x + b2y c2z= q

                                    a3x + b3y c3z = r

            In a matrix form we have

            edu.uptymez.com  edu.uptymez.com =  edu.uptymez.com

edu.uptymez.com

E.g. using Cramer’s rule   Solve  x + 2y + z = 6
2x + y – z = 3
3x – y + 2z = 5

            Solution

            edu.uptymez.com

edu.uptymez.com

                        = 1 (2 – 1) – 2 (4 + 3) + 1 (-2 – 3)

                        = 1 – 14 + -5 = -18

edu.uptymez.com

             edu.uptymez.com

                 = 6 (2 – 1) – 2 (6 + 5) + 1 (-3

                 = 6 – 22 + – 8

                 edu.uptymez.com= -24

            edu.uptymez.com

            edu.uptymez.com= 1 edu.uptymez.com – 6 edu.uptymez.com + 1 edu.uptymez.com

                        = 1 (6 + 5) – 6 (4 + 3) + 1 (10 – 9)

                        = 11 – 42 + 1

                      edu.uptymez.com  = -31 + 1 = -30

edu.uptymez.com

edu.uptymez.com


II. Inverse method

            a1x + b1y + c1z = p

            a2x + b2y + c2z = q

            a3x + b3y + c3z = r

edu.uptymez.com

                   A edu.uptymez.com = edu.uptymez.com

            AA-1
edu.uptymez.com = A-1
edu.uptymez.com

                 I  edu.uptymez.com = A-1
edu.uptymez.com

                   edu.uptymez.com = A-1
edu.uptymez.com


E.g: solving using inverse method

                        x + 2y + z
= 6

                        2x + y – z = 3

                        3x – y + 2z = 5

                        edu.uptymez.com edu.uptymez.com = edu.uptymez.com

                 A =edu.uptymez.com

            edu.uptymez.com = 1 edu.uptymez.com – 2 edu.uptymez.com + 1 edu.uptymez.com

                        = 1 (2 – 1) – 2 (4 + 3) + 1 (-2 – 3)

                        = 1 – 14 + (-5)

                        = -13 – 5

                  edu.uptymez.com= -18

                        A =  edu.uptymez.com

            Cof 1 = + 1edu.uptymez.com          cof 2 = -1 edu.uptymez.com

                        = +1 (2 – 1)                  = 1 (4 + 3)

                        = 1                              = -7

            Cof 1 = + 1 edu.uptymez.com                cof 2 = -1 edu.uptymez.com

                        = + (-2 – 3)                = -1 (4 + 1)

                        = -5                             = -5

            Cof 1: + 1 edu.uptymez.com                  cof -1 = -1 edu.uptymez.com

                        = +1 (2 – 3)               = -1 (-1 – 6)

                        = -1                             = 7

            Cof 3: + 1edu.uptymez.com                  cof -1= -1 edu.uptymez.com

                        = + 1 (-2 – 1)             = -1 (-1 – 2)

                        = -3                                         = 3

            Cof 2: + 1 edu.uptymez.com

                        = + 1 (1 – 4)

                        = -3

            Matrix of cofactors, C

        C  =    edu.uptymez.com


Note: Adj A = CT
Adj A =  edu.uptymez.com

Inverse of A
edu.uptymez.com

    A-1  =    edu.uptymez.com   edu.uptymez.com                                                                                              

              A-1   =edu.uptymez.com 


edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

            = edu.uptymez.com

            = edu.uptymez.com = edu.uptymez.com

            = edu.uptymez.com = edu.uptymez.com

Exercise

1.  a) Given A = edu.uptymez.com, and B = edu.uptymez.com,  Find A + B

      b) If  A = edu.uptymez.com  is singular find the value of k

      c) Find the inverse of B = edu.uptymez.com

    d) Solve edu.uptymez.com


2.  Using i) Determinant
ii) Inverse, solve for x, y and z

               3x – y + z = 2

               x + 5y + 2z = 6

               2x + 3y + z
= 0

3.  a) solve
edu.uptymez.com
i) Using determinant
ii) inverse

      b) If A =edu.uptymez.com, B = edu.uptymez.com and

                        C = edu.uptymez.com

                        Show that (A + B – 2C) is singular

      c) Solve x + y + z
= 6

                        3x – 2y – z
= -1

                        2x + 4y + 3z = 19  Using i) determinant

                                                                 ii) Inverse

4.  Solve,  2x – 3y + z = 3

                -x + 4y + 3z = 16

                3x + 2y – 2z = 1

5.  A transformation is given by the matrix M where M = edu.uptymez.com Find the (a) image of (-2, 5) under M (b) Inverse of M.

6.  If T is linear transformation such that T = edu.uptymez.com and T (x, y) = (3y, 5x),  Find T hence evaluate T (1, 2)

            b) Use inverse method to solve

            edu.uptymez.com

7.  a) Given A = edu.uptymez.com. B = edu.uptymez.com,  Find AB and BA

     b) Find the value of x,y,w and z

                        3 edu.uptymez.com = edu.uptymez.com + edu.uptymez.com

Share this post on: